The Balance Sheet of Western Philosophy in This Century (American Journal of Islam and Society, 1985)
Today, Western philosophy is all too close to its origins because it has neverreally answered the questions that brought about its birth. These questionsare: What is the meaning of life and death? What is the source and what isthe vocation of our freedom? How to act in order to fulfill the patterns ofGod? Such essential questions of philosophy are raised only by man, and properlyso. For only man cannot live without raising them.In nature, every being has a place and a function which are not of his ownchoosing. Every creature is subject to the law of God: a stone must fall whenreleased, a plant must grow when nourished; an animal must follow its instinct.All of them obey and fulfill this divine law without choice or questioning.With man, however, a new realm begins. He is the only creature that Godhas endowed with the choice of either disobeying or fulfilling that law aftera free, deliberate, and responsible decision.The Holy Qur’an says: “We have offered Our trust to the heavens, to earthand mountains. But they all rejected it in fear and trembling. Only man aroseto accept and carry that trust. He alone is unjust and ignorant (33:72).It was thus that human history began, a history which man himself makes,unlike all other creatures which fulfill the law of necessity.In order to regain this lost unity, that is to say, in order to integrate himinto the whole of creation, and thus give his life and death their place andmeaning in the divine order, man created all sorts of myths. But he also receiveddivine assistance through the revelations brought by the prophets of everypeople.In the sixth century after Christ, throughout Asia, the great myths ofMesopotamia and Egypt, the wise sayings of the Upanishads of India, andthose of Chinese Taoism raised and considered the basic problems of theultimate reality of this world, its meaning and significance, our role in it, ...